2022
DOI: 10.1542/peds.2022-057092f
|View full text |Cite
|
Sign up to set email alerts
|

Responsive Feeding for Preterm or Low Birth Weight Infants: A Systematic Review and Meta-analysis

Abstract: BACKGROUND AND OBJECTIVES Responsive feeding may improve health outcomes in preterm and low birth weight (LBW) infants. Our objective was to assess effects of responsive compared with scheduled feeding in preterm and LBW infants. METHODS Data sources include PubMed, Scopus, Web of Science, CINAHL, LILACS, and MEDICUS. Randomized trials were screened. Primary outcomes were mortality, morbidity, growth, neurodevelopment. Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This decision was informed by evidence of small benefits from responsive feeding on decreased length of hospital stay (very low certainty) but also small harms from responsive feeding on decreased weight gain until discharge (low certainty). 23 The trials included in the review used various feeding schedules; the GDG suggested that 2–3 hourly scheduled feedings may be used, as this is a commonly used and feasible schedule. A recommendation could not be made on feeding after hospital discharge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This decision was informed by evidence of small benefits from responsive feeding on decreased length of hospital stay (very low certainty) but also small harms from responsive feeding on decreased weight gain until discharge (low certainty). 23 The trials included in the review used various feeding schedules; the GDG suggested that 2–3 hourly scheduled feedings may be used, as this is a commonly used and feasible schedule. A recommendation could not be made on feeding after hospital discharge.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen new systematic reviews were commissioned to assess topics not addressed in existing reviews and 21 additional existing systematic reviews and meta analyses were assessed by the GDG ( Supplementary Table S2 ). 7 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 The quality of the scientific evidence for each intervention was graded using the Grading of Recommendations Assessment, Development and Evaluation (GRADE), 40 and evidence was categorised as high, moderate, low and very low certainty. The Confidence in the Evidence from Reviews of Qualitative research (CERQual) 41 approach was used for qualitative evidence.…”
Section: Methodsmentioning
confidence: 99%